Childhood onset arthritis is associated with an increased risk of fracture: a population based study using the General Practice Research Database. Issue 8 (20th April 2006) - Burnham, J M; Shults, J; Weinstein, R; Lewis, J D; Leonard, M B
Abstract : Background: Childhood onset arthritis is associated with low bone mass and strength. Objective: To determine whether childhood onset arthritis is associated with greater fracture risk. Methods: In a retrospective cohort study all subjects with onset of arthritis between 1 and 19 years of age in the United Kingdom General Practice Research Database were identified. As controls, all sex and age matched subjects from a practice that included a subject with arthritis were included. Incidence rate ratios (IRRs) for first fracture were generated using Mantel-Haenszel methods and Poisson regression. Results: 1939 subjects with arthritis (51% female) and 207 072 controls (53% female) were identified. The median age at arthritis diagnosis was 10.9 years. A total of 129 (6.7%) first fractures were noted in subjects with arthritis compared with 6910 (3.3%) in controls over a median follow up of 3.90 and 3.95 years in the subjects with arthritis and controls, respectively. The IRR (95% confidence interval) for first fracture among subjects with arthritis, compared with controls, according to the age at the start of follow up were 1.49 (0.91 to 2.31) for age <10 years, 3.13 (2.21 to 4.33) at 10–15 years, 1.75 (1.18 to 2.51) at 15–20 years, 1.40 (0.91 to 2.08) at 20–45 years, and 3.97 (2.23 to 6.59) at >45 years. Conclusions: Childhood onset arthritis is associated with a clinically significant increased risk of fracture in children, adolescents and, possibly, adults. Studies are urgently needed to characterise the determinants of structural bone abnormalities in childhood arthritis and devise prevention and treatment strategies.